2010
DOI: 10.1089/ten.tea.2009.0207
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Goat Femur Segmental Defects with Silica-Coated Hydroxyapatite—One-Year Follow-Up

Abstract: Segmental bone defects caused by tumor resections, trauma, and skeletal abnormalities such as osteomyelitis remain a major problem in orthopedics because of the lack of predictability in attaining functional bone after the treatment. The objective of this study was to propose an indigenous porous biodegradable triphasic ceramic (calcium silicate, tricalcium phosphate, and hydroxyapatite [HA])-coated HA (core) (HASi) for the repair of such segmental defects. With respect to the synthesis of HASi, HA blocks were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…7F), and that unilateral cortical bone not fused perfectly in the SAP/DBM (Fig. 7H); we suppose that the healing time of 16 weeks is relatively short, compared with 6-12 months (38,39).Regardless, these results indicated that the approach of immediate implantation after construction induced satisfactory outcomes. Moreover, this approach possessed advantages over traditional tissue engineering constructs, such as convenience, low risk, time savings, and ethical compliance.…”
Section: Discussionmentioning
confidence: 81%
“…7F), and that unilateral cortical bone not fused perfectly in the SAP/DBM (Fig. 7H); we suppose that the healing time of 16 weeks is relatively short, compared with 6-12 months (38,39).Regardless, these results indicated that the approach of immediate implantation after construction induced satisfactory outcomes. Moreover, this approach possessed advantages over traditional tissue engineering constructs, such as convenience, low risk, time savings, and ethical compliance.…”
Section: Discussionmentioning
confidence: 81%
“…Silicate has a scientifically proven osteo-stimulating effect. 11,12 Silicate correspondingly actively takes effect during the remodeling of the woven bone to become lamellar bone. During this process, SiCaP is reabsorbed.…”
Section: Methodsmentioning
confidence: 99%
“…Most interestingly, silicon‐substituted HA (HASi) has shown both an increased in vivo dissolution rate and bone apposition to the implant surface compared with pure HA . Several comparative studies have demonstrated the efficacy of silica in stimulating bone cell function and its presence facilitates bone formation and ingrowth, and ultimately bone bonding in vivo …”
Section: Introductionmentioning
confidence: 99%
“…21,24 Several comparative studies have demonstrated the efficacy of silica in stimulating bone cell function and its presence facilitates bone formation and ingrowth, and ultimately bone bonding in vivo. 25,26 A porous (50-500 μm) bioactive triphasic hydroxyapatite (HASi) was developed by incorporating HA and silica. The major phase of HASi is HA, whereas the outer layer shows peaks of HA (Ca 5 [PO 4 ] 3 [OH]), tricalcium phosphate (Ca 3 (PO 4 ) 2 ), and calcium silicate (Ca 2 SiO 4 ).…”
Section: Introductionmentioning
confidence: 99%